STUDI PENDAHULUAN : INDUKSI KALUS EMBRIOGENIK DARI EKSPLAN DAUN Echinaceae purpurea - Meynarti Sari Dewi Ibrahim; N. Nova Kristina; Nurliani Bermawie (Pusat Penelitian dan Pengembangan Perkebunan, 2004)
Echinaceae is an introduced medicinal plant used to improve immune system of the body. Lately, interest on Echinaceae increased, however, good plant material for development is limited. One method to multiply plant material is the in vitro culture, so that research and development especially in vitro multiplication is required. The aim of the experiment is to procure a medium for the induction of embryonic callus and the technique of regeneration. The experiment is conducted at the Laboratory of Breeding and Genetic Resources, ISMECRI from January to December 2002, consisted of 2 steps, namely(1). Embryonic callus induction, (2). Callus regeneration. In the first step, explants were transferred into MS medium enrich with BA 0,1 mg/l + 2,4 D 0,5 mg/l and a combination medium of MS and LS medium supplemented with glutamine + BA (0,1 mg/l; 0,2 mg/l) + 2,4 D (0,5mg/l ; 1 mg/l). In the second step, regeneration was conducted on medium MS combined with LS + BA (0 mg/l + 0,2 mg/l + 0,4 mg/l), MS combined with LS + Kinetine (0,2 mg/l; 0,4 mg/l). The results showed that embryonic callus was obtained from culture of leaf explants on MS medium combined with LS. The best treatment for step regeneration was MS combined LS + BA 0,4 mg/l for shoot formation while MS combined LS + kinetine 0,4 mg/l induced root formation.